Communicative Competence as a Subjective Determinant: Globalization and Personal Aspects - Tetyana Pantiuk; Mykola Pantiuk; Iryna Voloshanska; Zoriana Burkovska (Vasyl Stefanyk Precarpathian National University, 2017)
The content and the specific process of communicative competence formation of the individuality are justified in the article; social determinants that determine the need to improve this process and harmonization with the needs of society and individuality are defined. The educational, psychological, philosophical sources are analysed, the main directions of research on definite problem are characterized. The essence of communicative competence as the educational phenomenon is found; the importance of communicative competence in today's conditions is proved. The attention is paid to the main principles and methods of communicative competence of the individuality.